Globalists: Heredity plutocracy and capital right protection - Šutović, Milojica (Sociološki pregled, 2023)
As an extension of colonialism, globalization is globalists’ “controlled democracy” founded on the limited participation. It is the rule of concealed totalitarianism of political single-mindedness, for the sake of protecting the global right of capital, profit maximization, rationalization of the neoliberal ideology of domination, the rule of the smaller part of one percent of the richest in the order or real inequality, meaninglessness of the general right of vote by reducing “one vote to one dollar, one euro, one dinar”. This includes the formation of hereditary plutocracy of the “wild”, gangster capitalism, in which the majority of global/local population lives most of their lives in a private dictatorship unrestricted b anything, both of surveillance and therapeutic capitalism, and of meritocratic or hybrid state capitalism, apparent freedom and real exploitation, where globalists mediate about “colonizing Mars or the end of the world and the poor – about the end of the month”.
Keywords: globalists; globalization; hereditary plutocracy; capital right protection; inequality; exploitation